A latent profile analysis for teacher education students’ learning: an overview of competencies in self-regulated learning - Janina Schel; Barbara Drechsel (Frontiers in Psychology)
IntroductionEspecially for teacher education students, competencies in self-regulated learning are of great importance: for their own learning during their studies, as well as for the diagnosis and support of their future students. This study aims to investigate the competencies and developmental potentials (currently low-developed areas that hold the potential for improvement) of these students’ self-regulated learning processes.MethodsData from N = 240 teacher education students regarding the preaction, action, and postaction parameters of the self-regulated learning process were analyzed.ResultsThrough latent profile analysis (LPA), five self-regulated learning profiles were extracted and labeled as follows: process-oriented competent, preaction-volitional competent, action-cognitive competent, repetitive-low reflective, and avoiding-unreflective. The profiles were validated by learning success and goal orientation. Higher-competency profiles demonstrated better learning success and more favorable goal orientations than lower-competency profiles.DiscussionThe person-centered approach of this study can help develop differentiated interventions based on learning profiles to promote self-regulated learning competencies in teacher education students, ensuring that interventions can be designed as efficiently as possible. Further potentials and limitations of the approach are discussed.